Thermal response of silicon during virtual laser micromachining - Muhammad Hasri, Ibrahim (2009)
This project presents thermal response of silicon during virtual laser micromachining based on finite element method. Predictable models were developed using ALGOR FE code to simulate laser micromachining and to predict temperature distribution in silicon due to laser material interaction. Two FE models, linear and circular cutting were developed. Thermal properties of silicon were taken from literature. Time dependent heat flux was defined at each node along cutting line, laser velocity was designed by model distance and time interval. Transient heat transfer analysis was used to simulate laser micromachining. Process parameters considered were laser power, velocity and plasma gas effect. Total of 28 simulations were done. The FE model was validated from published report. Results qualitatively were found to be agreeable. Crucial factors are found to be pulse energy and moving velocity in reducing thermal cracks and thermal debris. This virtual work can significantly reduce the cost and time for process development in industry, and improve product reliability.